Cardiovascular disease related circulating biomarkers and cancer incidence and mortality: is there an association?. Issue 10 (1st September 2021) - Jovani, Manol; Liu, Elizabeth E; Paniagua, Samantha M; Lau, Emily S; Li, Shawn X; Takvorian, Katherine S; Kreger, Bernard E; Splansky, Greta Lee; de Boer, Rudolf A; Joshi, Amit D; Hwang, Shih Jen; Yao, Chen; et al.
Abstract: Aims: Recent studies suggest an association between cardiovascular disease (CVD) and cancer incidence/mortality, but the pathophysiological mechanisms underlying these associations are unclear. We aimed to examine biomarkers previously associated with CVD and study their association with incident cancer and cancer-related death in a prospective cohort study. Methods and results: We used a proteomic platform to measure 71 cardiovascular biomarkers among 5032 participants in the Framingham Heart Study who were free of cancer at baseline. We used multivariable-adjusted Cox models to examine the association of circulating protein biomarkers with risk of cancer incidence and mortality. To account for multiple testing, we set a 2-sided false discovery rate <0.05. Growth differentiation factor-15 (also known as macrophage inhibitory cytokine-1) was associated with increased risk of incident cancer [hazards ratio (HR) per 1 standard deviation increment 1.31, 95% CI 1.17–1.47], incident gastrointestinal cancer (HR 1.85, 95% CI 1.37–2.50), incident colorectal cancer (HR 1.94, 95% CI 1.29–2.91), and cancer-related death (HR 2.15, 95% CI 1.72–2.70). Stromal cell-derived factor-1 showed an inverse association with cancer-related death (HR 0.75, 95% CI 0.65–0.86). Fibroblast growth factor-23 showed an association with colorectal cancer (HR 1.55, 95% CI 1.20–2.00), and granulin was associated with haematologic cancer (HR 1.61, 95% CI 1.30–1.99). Other circulating biomarkers of inflammation, immune activation, metabolism, and fibrosis showed suggestive associations with future cancer diagnosis. Conclusion: We observed several significant associations between circulating CVD biomarkers and cancer, supporting the idea that shared biological pathways underlie both diseases. Further investigations of specific mechanisms that lead to both CVD and cancer are warranted. Graphical Abstract: